The Effect of Using Internet-based Project Work toward Students' Vocabulary Mastery - Yulia Nugrahini (EDUCATION AND LINGUISTICS KNOWLEDGE JOURNAL, 2021)
English is an international language. Everyone is competing to master foreign language, especially English language as a communication tool in this era of globalization. As foreign language, it has many problems faced by Indonesian students, especially learning vocabulary. They are able to understand the teachers’ explanation, but it cannot stand any longer in their mind and especially for junior high school students. Vocabulary is one of the language component that should be learned by students, so they are able to accept the English material well. Therefore, the implementation of teaching media is one of the most important strategies in teaching learning process. The research findings in this research are the scores of vocabulary before and after being taught by using Internet-based Project Work. The results showed that the mean of total scores of students’ vocabulary mastery before being taught using Internet-based Project Work was (72,51). While the mean of total scores of students’ vocabulary mastery after they are taught using Internet-based Project Work was (83,16) . It was proved with the t-test analysis that used by the researcher can be shown the result tcount =(11,641), The value of “t” on the t score table t0,05 =(2.045). Based on the results above, alternative hyphotesis (Ha) states there is significant different score of student’s vocabulary mastery by using Internet-based Project Work is accepted, while the null hyphotesis (Ho) that states there is no significant different score of student’s vocabulary mastery is rejected. Finally, it can be concluded that Internet-based Project Work is effective media in teaching English vocabulary to junior high school, especially for eight grade students of SMPN 1 Durenan.